A new Brachyrhamdia (Siluriformes: Heptapteridae) from Rio Japurá basin, Brazil, with comments on its phylogenetic affinities, biogeography and mimicry in the genus - Slobodian, Veronica; Bockmann, Flávio Alicino (Zootaxa, 2013)
Brachyrhamdia thayeria is herein described as a new heptapterid species from Rio Japurá, a left margin tributary of the Rio Solimões, Amazonas basin, Brazil. The new species is diagnosed from all its congeners by having a putative autapomorphy: dark oblique stripe across the caudal peduncle, originating below the anterior half of adipose fin and ending at base of rays of ventral caudal-fin lobe. Brachyrhamdia thayeria is considered closely related to B. imitator and B. rambarrani with which it shares a low vertebral number and absence of lateral stripe along trunk. The new species shares exclusively with B. rambarrani the presence of a dark conspicuous bar along the dorsolateral region of trunk, a putative synapomorphy. Brachyrhamdia are distributed in lowland regions of northern South America where they inhabit small streams with running waters. The new species appears to have a mimetic association with the syntopic callichthyid Corydoras arcuatus. Herein, we argue in favor of the hypothesis that the interaction between species of Brachyrhamdia and Pimelodella or Corydoras is Müllerian mimicry.